Laser generation of XeCl exciplex molecules in a longitudinal repetitively pulsed discharge in a Xe – CsCl mixture; Quantum Electronics; Vol. 45, № 12 - Boychenko A. M. Aleksandr Mikhaylovich (2015, 2015)
Title screen